The Role of The Habits of Early Bedtime As A Form of Discipline Character Development on The Academic Achievement of Elementary School Students - Juliati; Salim, Herli; Arisetyawan, Andika (International Conference on Elementary Education, 2025)
This study aims to analyze the role of early bedtime habits as a form of disciplined character development on elementary school students' academic achievement. The background of this study stems from the phenomenon of declining student learning quality due to late sleeping habits, which impacts concentration, motivation, and readiness to learn at school. Early sleeping not only affectsphysiological and cognitive aspects but also reflects the formation of discipline as part of character education in elementary schools. This study used a quantitative correlational approach involving 22 fourth-grade students of Kramatwatu 2 Elementary School as the research sample. Data were collected through a questionnaire on student sleep habits and documentation of report card grades as an indicator of academic achievement. Data analysis was performed using the Pearson correlation test using SPSS version 29. The results showed a positive but insignificant relationship between early sleep habits and students' academic achievement (r = 0.095; p > 0.05). This indicates that although early sleep habits contribute to learning readiness and the formation of disciplined character, other factors such as learning motivation, parental support, and the learning environment also influence students' academic achievement. This study emphasizes the importance of implementing early sleep habits as part of character education in elementary schools to support the balance between physical health, mental readiness, and students' academic success.